Forudsigelser om skyld og straffastsættelse - Christian M. Dahl; Rasmus H. Wandall; Simon Wittrock (Nordisk Tidsskrift for Kriminalvidenskab)
Abstract A certain degree of predictability in criminal law is important for the overall functionality of the criminal justice system. For victims, the accused, and their relatives, predictability – and the lack thereof – has a more concrete and immediate impact. The lack of predictability of how and when cases are handled, and with what outcome, installs an uncertainty of significant events for those involved in the case. This effectively limits those persons’ abilities to make decisions about their cases and their lives. Existing literature correspondingly shows that the process of a criminal case, its duration, and the uncertainty about the outcome represent a significant burden to those involved. There is a real need for legal and procedural empowerment. In this paper, we examine how statistical models increase predictability regarding sentencing outcomes and find that our models reduce the uncertainty of case outcomes for the accused, the victims, and their relatives.